2015
DOI: 10.1007/s10875-015-0170-4
|View full text |Cite
|
Sign up to set email alerts
|

A Homozygous CARD9 Mutation in a Brazilian Patient with Deep Dermatophytosis

Abstract: Deep dermatophytosis has been described in HIV and immunosuppressed patients. Recently, CARD9 (caspase recruitment domain-containing protein 9) deficiency has been reported in individuals with deep dermatophytosis previously classified as "immunocompetent". We report a 24-year-old Brazilian male patient with deep dermatophytosis born to an apparently non-consanguineous family. The symptoms started with oral candidiasis when he was 3 years old, persistent although treated. At 11 years old, well delimited, desqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 15 publications
(30 reference statements)
1
59
0
1
Order By: Relevance
“…Other fungal infections included mostly superficial dermatophytosis, without the deep dermatophytosis seen in some CARD9-deficient patients. 14,68 Invasive infections by a variety of yeasts, molds, and dimorphic fungi were observed in some patients. 23,34,37,40 Cutaneous and bronchopulmonary infections caused by S aureus were also observed, as in patients with AD-HIES.…”
Section: Discussionmentioning
confidence: 99%
“…Other fungal infections included mostly superficial dermatophytosis, without the deep dermatophytosis seen in some CARD9-deficient patients. 14,68 Invasive infections by a variety of yeasts, molds, and dimorphic fungi were observed in some patients. 23,34,37,40 Cutaneous and bronchopulmonary infections caused by S aureus were also observed, as in patients with AD-HIES.…”
Section: Discussionmentioning
confidence: 99%
“…To date, all clinically reported homozygous or compound heterozygous carriers with either no CARD9 expression or CARD9 loss-of-function alleles are more susceptible to fungal infection (Drewniak et al, 2013; Gavino et al, 2014; Gazendam et al, 2014; Glocker et al, 2009; Grumach et al, 2015; Herbst et al, 2015; Jachiet et al, 2015; Lanternier et al, 2015a; Lanternier et al, 2015b; Lanternier et al, 2013; Wang et al, 2014). Our results from Trim62 −/− mice suggest that TRIM62-mediated regulation of CARD9 activation is critical in the context of fungal infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Card9 signaling pathway appears to be the central mammalian host defense mechanism against fungi, given that multiple genetic studies in humans have recently identified that several Card9 loss-of-function defects are causative for several fungal diseases, including various types of mucocutaneous candidiasis; superficial, extensive, and deep dermatophytosis with Trichophyton spp. ; subcutaneous phaeohyphomycosis; invasive Candida infections of the digestive tract and central nervous system; Candida endophthalmitis and osteomyelitis; and disseminated Exophiala disease of the liver, brain, and lung (Grumach et al., 2015, Pérez de Diego et al., 2015). …”
Section: Discussionmentioning
confidence: 99%